Розподіл допустимого тиску на ґрунт ходових систем колісних тракторів за територією України - Ребров, Олексій Юрійович (НТУ "ХПІ", 2018)
Запропоновано методику оцінки впливу на ґрунт ходових систем колісних тракторів згідно встановленому розподілу за територією України допустимого тиску на ґрунт колісних тракторів відповідно до вимог стандарту та урахуванням особливостей ґрунто-кліматичних умов та фактичних середньобагаторічних параметрів вмісту вологи в ріллі в середньобагаторічні терміни проведення робіт під час підготовки ґрунту під ранні ярові культури навесні та під озиму пшеницю в літньо-осінній період.

The paper proposes a methodology for estimating theimpact on the soil of the running systems of wheeled tractors according to the established distribution throughout the territory of Ukraine of permissible pressure on the soil in accordance with standard requirements and taking into account the peculiarities of soil and climatic conditions and theactual long-term average moisture content parameters in arable land during the long-term average work period of preparing the soil for early spring crops and under winter wheat in the summer-autumn period. The maximum pressure on the soil for modern tires of agricultural tractors is in the range of 78-177 kPa. At such a maximum pressure, theprobability of a tire fulfilling the requirements of the standard for the performance of running gears on the soil will be in the range from 0.078-0.104 to 0.698-0.730. It is necessary to use conversion track systems or crawler tractors to ensure an impact on the soil within the limits of permissible in the cultivation of agricultural land, the area of which is more than 27-30 % of Ukraine's territory. The use of conversion track systems allows to reduce the maximum pressure on the soil by 65 %, which greatly improves the environmental friendliness of the tractors.
Distribution of admissible pressure of running gears of collector tractors on the soil throughout the territory of Ukraine
Keywords: максимальний тиск на ґрунт; гранулометричний склад; стискання; ґрунто-кліматичні зони; wheeled tractor; running gears; maximum pressure on the soil; permissible pressure on the soil; parameters of moisture content in arable land